What is hiding behind S100 protein and SOX10 positive oncocytomas? Oncocytic pleomorphic adenoma and myoepithelioma with novel gene fusions in a subset of cases - Baněčková, Martina; Uro-Coste, Emmanuelle; Ptáková, Nikola; Šteiner, Petr; Stanowska, Olga; Benincasa, Giulio; Colella, Giuseppe; Vondrák, Jan; Michal, Michal; Leivo, Ilmo; Skálová, Alena (Human pathology, 2020)
Oncocytomas (OCs) in salivary glands are rare benign tumors composed of mitochondria-rich epithelial cells (oncocytes), mostly localized in the parotid gland. The treatment of choice is simple excision. Extensive oncocytic metaplasia of pleomorphic adenoma (PA) and myoepithelioma (ME) can be diagnostically challenging and may camouflage the correct diagnosis. These tumors should be treated more carefully compared with OC, given the risk of frequent recurrences and the possibility of malignant transformation. We have investigated 89 oncocytic lesions from our files, including OC (n = 74) and metaplastic oncocytic variant of PA/ME (n = 15). All OCs were stained for S100 protein and SOX10. The tumors with immunohistochemical expression of one or both markers were tested by next-generation sequencing (NGS). The NGS results were confirmed by reverse transcription-polymerase chain reaction (RT-PCR) and/or fluorescence in situ hybridization (FISH). Ten cases originally diagnosed as OC, and 1 low-grade uncertain oncocytic tumor (11/74) revealed nuclear-cytoplasmic and/or nuclear positivity for S100 protein and/or SOX10, respectively. Fusion transcripts CHCHD7-PLAG1 and GEM-PLAG1 were found in 2 cases (1 fusion in each), and these were confirmed by RT-PCR and PLAG1 break-apart FISH probe, respectively. Another 5 cases were positive for PLAG1 rearrangement by FISH. In the control group of 15 oncocytic PA/ME, 4/15 tested tumors harbored gene fusions including NFT3-PLAG1, CHCHD7-PLAG1, FBXO32-PLAG1, and C1orf116-PLAG1 (1 fusion in each case) as detected by NGS. Two fusions were confirmed by RT-PCR, 1 case by FISH, and 1 case was not analyzable by FISH. We additionally tested 24 OCs negative for S100 protein and SOX10 by immunohistochemistry (IHC) and by FISH for rearrangement of PLAG1 gene, but none of them were positive. SOX10 and/or S100 protein immunopositivity in conjunction with rearrangement of the PLAG1 gene assisted in reclassification of a subset of oncocytomas as oncocytic variants of PA and ME. Therefore, we recommend to include S100 protein and SOX10 IHC when diagnosing tumors with predominantly oncocytoma-like differentiation. In addition, by NGS, 3 new gene fusions were detected in oncocytic ME, including NTF3-PLAG1, FBXO32-PLAG1, and GEM-PLAG1, and a new fusion C1orf116-PLAG1 was detected in oncocytic PA.
Keywords: oxyfilní adenom; Male; Salivary Gland Neoplasms; Adenoma, Oxyphilic; lidé středního věku; retrospektivní studie; senioři nad 80 let; myoepiteliální nádor; Aged, 80 and over; Pleomorphic adenoma; nádorové biomarkery; proteiny S100; PLAG1; Humans; Oncocytoma; SOXE Transcription Factors; Middle Aged; Biomarkers, Tumor; pleomorfní adenom; senioři; Adenoma, Pleomorphic; mužské pohlaví; nádory slinných žláz; Female; Oncogene Fusion; S100 protein; Aged; ženské pohlaví; Myoepithelioma; Retrospective Studies; SOX10; S100 Proteins; Adult; onkogenní fúze; dospělí; lidé; transkripční faktory SOXE